Design, Construction, and Programming of a Mobile Robot Controlled by Artificial Vision - Urrea-Onate, E (IGI Global, 2017)
The design, construction and programming of a mobile robot controlled by means of artificial vision, capable of recognizing, grabbing and moving specific objects in a completely autonomous way is presented, together with the conceptual and theoretical-practical grounds for the work. A mechanically robust robot is built and a system is designed, allowing the mobility of two sensors jointly, i.e., artificial vision camera and distance sensor. This makes it possible to improve the range of artificial vision, over approximately 180°, achieving precise positioning of the mobile robot. The artificial vision camera, CMUCam 2, provides the mobile robot with great autonomy thanks to its excellent interaction with its surrounding world. Having a mobile robot like this will allow interesting developments to be made in various areas of mobile robotics. © 2017 IGI Global. All rights reserved.